Utilitarian VS Hedonic Value: Which is More Influential for Indonesian Consumers in Increasing Purchase Intention in E-Commerce? - Nisrina Sherin Caesalpinia; Bethani Suryawardani (Journal of Consumer Sciences)
Background: Companies should leverage the rapid growth of online shopping in Indonesia to enhance customer experiences and boost sales. Live streaming plays a crucial role in influencing customer behavior, making it a valuable strategy for increasing purchasing interest.